2014
DOI: 10.1111/cen.12420
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and radiological relationships in patients with pheochromocytoma: lessons from a case control study

Abstract: SummaryBackground An elevation of fractionated plasma or urinary metanephrine (MN) or nor-metanephrine (NMN), collectively called metanephrines (MN and NMN), >4-fold above the upper limit of normal (ULN) is usually considered to be diagnostic for pheochromocytoma (PHEO). There are a greater number of false positive results when the elevations are more modest. Aim To identify biochemical and radiological features in PHEOs with modest elevations (<4-fold above ULN) of metanephrines. Methodology We retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
(106 reference statements)
2
15
0
Order By: Relevance
“…Although the authors concluded that these large functioning adrenal myelolipomas were producing catecholamines, another interpretation would be as in our case that it was related to sympathetic activation (4,5,12). The findings in our case are consistent with the recent report by Kannan et al (11). We present evidence that the plasma normetanephrines are <4-fold upper normal and the embolization and acute illness associated with this tumor resulted in a suppressible sympathetic release of catecholamines rather than autonomous secretion of them.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Although the authors concluded that these large functioning adrenal myelolipomas were producing catecholamines, another interpretation would be as in our case that it was related to sympathetic activation (4,5,12). The findings in our case are consistent with the recent report by Kannan et al (11). We present evidence that the plasma normetanephrines are <4-fold upper normal and the embolization and acute illness associated with this tumor resulted in a suppressible sympathetic release of catecholamines rather than autonomous secretion of them.…”
supporting
confidence: 93%
“…Hemorrhage within the tumor might increase the tissue density and HU, as was seen in this case (1,2). Pheochromocytoma precontrast attenuation values are generally >10 HU (11).…”
Section: Discussionmentioning
confidence: 54%
“…In our experience the lowest attenuation value for adrenal PHEO has been 17 HU. 30 There has been a report of unenhanced CT attenuation values less than 10 HU in 2 patients with symptomatic adrenal PHEO. 31 However, these tumors were very small, less than 1.5 cm, and one of the reported patients had adrenal medullary hyperplasia on pathology.…”
Section: Noncontrast Computed Tomography Attenuation Coefficientmentioning
confidence: 99%
“…Based on the accumulating data in the literature and our own experience, we only perform biochemical investigation for PHEO in patients with AIs in whom the CT attenuation value is greater than 10 HU. 30,32,33 Computed tomography washout and enhancement patterns…”
Section: Noncontrast Computed Tomography Attenuation Coefficientmentioning
confidence: 99%
See 1 more Smart Citation